The gift of therapy : An open letter to a new generation of therapists and their patients - Yalom, Irvin D. (Parennial, 2003)
This summation of Yalom's life thinking on the art of psychotherapy, presented in the form of 85 tips, is filled with personal techniques and clinical anecdotes. Yalom, who has 45 yrs of clinical experience, addresses the nature of the therapist-patient relationship, explores the ultimate concerns of death, the meaning of life, and freedom (encompassing responsibility and decisions), and issues that arise in the everyday conduct of therapy. He also discusses the role of dreams and the hazards and privileges of being a therapist. Some of his more controversial suggestions include (1) let the patient matter to you, (2) use your own feelings, (3) create a new therapy for each patient, (4) acknowledge your errors with the patient, and (5) avoid diagnosis. Yalom worries that the field of psychiatry is in a state of crisis--a crisis which will adversely affect the next generation of therapists and patients. From his perspective, the economically driven health-care system threatens the existence of extensive and thoughtful psychotherapy.